FAKTOR-FAKTOR PENYEBAB KERUSAKAN BAHAN PUSTAKA DI PERPUSTAKAAN SMA MUHAMMADIYAH 2 PONTIANAK - Ramadhan Saukani Caesatrio; Atiqa Nur Latifa Hanum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis final project discusses the "Factors Causing Damage to Library Materials in the Library of 2nd Muhammadiyah High School in Pontianak ". First problem, the factors that cause damage to library materials. Second, efforts to deal with damage to library materials. Third, the constraints on the maintenance and preservation of library materials. The purpose of this study is first, to describe the factors that cause damage to library materials. Second, to describe efforts to deal with damage to library materials. Third, to describe the constraints of care and preservation of library materials. This research is a descriptive qualitative study. The method of data collection uses observation, interviews, documentation, literature studies while the analytical techniques are carried out namely data reduction, data presentation and conclusions. The results of this study indicate that there are several factors that cause damage to library materials. Namely first, the characteristic factor of the collection material itself is paper. Second, environmental factors such as dust coming from the cement floor of the library. Third, human factors such as eating and drinking in the library, as well as acts of vandalism carried out by users. Therefore, it is necessary to take action to deal with damage to library materials. Namely first, cleaning the library space. Second, do education to provide understanding to users. Third, weeding library material. The activities of preservation and maintenance of library materials cannot be carried out optimally because of the limited number of human resources in the library itself.  Keywords: Cause of Damage, Library Material, Preservation